Effectiveness of syntactical teaching books judging on content feasibility, serving, language and graphic - Putrayasa, Ida Bagus (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of this study is to describe the effectiveness of the syntax of the syntactic (grammar) of the content of the type, unity, and sentence structure; eligibility, language worthiness, and graphic eligibility for elementary school students in Bali province. The data source used to be the subject in this research is the expert and practitioner/teacher of Grade VI Elementary School in Bali province. Meanwhile, the object of this research is the effectiveness of the syntax teaching book which includes elements: content feasibility, presentational feasibility, language worthiness, and grafapia eligibility. The method used to collect data is a poll method/questionnaire. The collected data is analyzed by a descriptive-qualitative technique. The results showed that the aspects of the teaching books ’Grammar of the Indonesian Elementary School’ which has received (1) eligibility, (2) Eligibility of content (type, unity, and sentence structure), (3) language eligibility, and (4) Eligibility the graphic is very good or very valid.